Field notes contributed by Fred Lesher, June 6, 1997 - Lesher, Fredet al (1997)
List of birds and locations contributed by Fred Lesher. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1997. Epson - sheet feed